KURIKULUM PENDIDIKAN ANAK USIA DINI - Imroatul Hasanah (Universitas Islam Balitar, 2015)
This article reviews philosophy of early stage children inperspectives of theory, beneficial, and law enforcement in educationcontext of in Indonesian government policy. Theoretically, earlychildhood is a golden era where children get benefits for thedevelopment of psychomotor and cognitive performance. This way,multiple intelligences are crucial potential teachers and parentsshould develop. The higher development early children wouldachieve is potential literacy where critical thinking, characters, andcapacity building would be relied upon. Government policy devotedto this context should inditace strong policy, such as curriculum forchildren and law enforcement ensuring children to receive theirrights and protection.